2019
DOI: 10.1101/571885
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Oncogenic signaling alters cell shape and mechanics to facilitate cell division under confinement

Abstract: When cells enter mitosis, they become spherical and mechanically stiffen. We used MCF10A cell lines as a model system in which to investigate the effect of induced oncogene expression on mitotic entry. We find that activation of oncogenic Ras V12 , for as little as five hours, changes the way cells divide. Ras V12 -dependent activation of the MEK-ERK signalling cascade alters acto-myosin contractility to enhance mitotic rounding. Ras V12 also affects cell mechanics, so that Ras V12 expressing cells are softer … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 45 publications
3
7
0
Order By: Relevance
“…In particular, we observed a softer, less contractile cortex in post-EMT interphase cells and a more contractile, stiffer cortex phenotype in post-EMT mitotic cells in comparison to the respective pre-EMT phenotype. Our observation that post-EMT interphase cells have a softer actin cytoskeleton is in agreement with a study by Osborne et al that reported softening of adherent cells upon EMT 43 and with reports that metastatic cancer cells are on average softer than healthy and non-metastatic cells 20,[44][45][46] . Here, we show for the first time opposite changes in cell cortex mechanics in interphase and mitotic cells upon EMT (Figure 2e-g).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In particular, we observed a softer, less contractile cortex in post-EMT interphase cells and a more contractile, stiffer cortex phenotype in post-EMT mitotic cells in comparison to the respective pre-EMT phenotype. Our observation that post-EMT interphase cells have a softer actin cytoskeleton is in agreement with a study by Osborne et al that reported softening of adherent cells upon EMT 43 and with reports that metastatic cancer cells are on average softer than healthy and non-metastatic cells 20,[44][45][46] . Here, we show for the first time opposite changes in cell cortex mechanics in interphase and mitotic cells upon EMT (Figure 2e-g).…”
Section: Discussionsupporting
confidence: 93%
“…Thus, it has been hypothesized that the actin cortex of cancer cells exhibits oncogenic adaptations that allow for ongoing mitotic rounding and division inside tumors 19 . In fact, it was shown that the human oncogene Ect2 contributes to mitotic rounding through RhoA activation 7,10 and that Ras overexpression promotes mitotic rounding 20 . Epithelial-mesenchymal transition (EMT) is a cellular transformation in which epithelial cells loose epithelial polarity and intercellular adhesiveness gaining migratory potential [21][22][23] .…”
Section: Introductionmentioning
confidence: 99%
“…The polyacrylamide gel used for cell compression was prepared as described in Matthews et al and Le Berre et al with modifications (Le Berre et al, 2014;Matthews et al, 2020). Briefly, 18 mm glass coverslips (Sangon, F518211) were treated with 10 l Binding-silane (Sangon, C500226) for 10 minutes and then were rinsed with 100% ethanol and air-dried.…”
Section: Elastic Polyacrylamide Gel Preparationmentioning
confidence: 99%
“…These cellular forces together lead to mitotic cell rounding that provides an ideal cell geometry to undergo mitosis and cytokinesis (Lancaster et al, 2013). Establishing and maintaining cell surface tension to sustain a minimum cell height for a functional cell geometry during mitosis is particularly important when cells are dividing in a physically confined tissue environment (Cattin et al, 2015;Matthews et al, 2020). Within a tissue environment, cells constantly experience mechanical stresses such as compressive stress from surrounding cells and the extracellular matrix.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation